Large and small holdings. A study of English agricultural economics. Transl. [from German] by R. Kenyon, with considerable additions by the author (Kelley etc., 1966)
With bibliogr., index and tabs. 1st ed. 1911. Original title: Entstehung und Rückgang des landwirtschaftlichen Grossbetriebs in England.